Trello as virtual learning environment and active learning organiser for PBL classes: An analysis under Bloom's Taxonomy - Uebe Mansur, Andre Fernando (2019)
Trello is a cloud app based on Kanban concept and also available for desktop mobile devices. The app has plenty of boards that help projects' development under SCRUM concept. Trello is not originally designed as a Virtual Learning Environment (VLE) but it is recurrently adopted by one of the paper authors as a VLE for Project-Based Learning (PBL) classes development. It is also used as a formative assessment platform. The present research brings a case study under Trello point of view about a PBL class from a specialisation program named Creativity & Innovation where students chose to develop a project related to a vegan pizza bike entrepreneur in a Brazilian Applied Science Institute. The students from this PBL class came from distinct study areas like Graphic Design, Business Administration, Social Communication, and Journalism as well as Production Engineering since the program has an interdisciplinary character. Active Learning was the core learning approach taking PBL as a framework for it. According to the methodology, the students collaboratively identified the steps for project development from the “pizza bike” to the business areas related to it. For instance: visual identity, digital marketing, financial and accountability, manufacturing, etc. After that, the students supported by a tutor proposed teams for each areas identifying team tasks. From the beginning until the last activity, Trello as a VLE was disruptively essential for project organisation as well as their project success. A model based on Bloom's Taxonomy and other authors were proposed for the results analysis and it was possible to conclude that Trello as an innovative VLE and PBL organiser seemed to be positive from the author´s/tutor´s perception to the students' feedback and project results.